MOTIVASI BELAJAR DALAM PEMBELAJARAN KONSTRUKTIVISTIK (Sebuah Kajian Teoretik Berdasarkan Teori Ekspektansi Vroom) - Semuel Nitbani (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2022)
One of the more realistic theories in the explanation of Constructivistic learning motivation is Vroom's Expectancy theory based on the principle in the relationship between the two. This relationship shows that, (1) students will be motivated to form their own abilities if there are external determinants that provide the possibility of achieving the results students want. (2) The process of forming self-ability by students takes place through stages that meet the requirements, are important, and convincing, in the psychological picture of students in the range of values ​​-1 to +1, i.e. the value of -1 is the student believes that the second result is impossible to achieve. without the first result, up to +1, indicating that the student believes that the first result is important and qualifies to achieve the second result. The principle of expectancy theory is congruent with Vygoutsky's constructivist theory in Scaffollding's perspective, which perceives the process as a series of convincing and qualified results. (3) The implementation of the concept of Vroom's Expectancy theory in constructivist learning takes place through the application of: (a) the concept of valence, namely belief in individual characteristics and student preferences in shaping their own abilities; (b) The instrumentalist concept, namely the fulfillment of requirements in each stage of learning; (c) The concept of expectation, namely the possibility of achieving learning outcomes provided by the teacher; (d) The concept of strength, namely the attractiveness of students to the learning outcomes they want. Student learning motivation applies in line with the degree of confidence in the achievement of the desired results of students. The greater the possibility of achieving the desired results, the stronger the motivation to learn.